Favoring Expression of Yak Alleles in Interspecies F1 Hybrids of Cattle and Yak Under High-Altitude Environments - Chen, Shi-Yi; Li, Cao; Luo, Zhihao; Li, Xiaowei; Jia, Xianbo; Lai, Song-Jia (Frontiers in Veterinary Science, 2022)
Both cis- and trans-regulation could cause differential expression between the parental alleles in diploid species that might have broad biological implications. Due to the relatively distant genetic divergence between cattle and yak, as well as their differential adaptation to high-altitude environments, we investigated genome-wide allelic differential expression (ADE) in their F1 hybrids using Nanopore long-read RNA-seq technology. From adult F1 hybrids raised in high-altitude, ten lung and liver tissues were individually sequenced for producing 31.6 M full-length transcript sequences. Mapping against autosomal homologous regions between cattle and yak, we detected 17,744 and 14,542 protein-encoding genes expressed in lung and liver tissues, respectively. According to the parental assignments of transcript sequences, a total of 3,381 genes were detected to show ADE in at least one sample. There were 186 genes showing ubiquitous ADE in all the studied animals, and among them 135 and 37 genes had consistent higher expression of yak and cattle alleles, respectively. Functional analyses revealed that the genes with favoring expression of yak alleles have been involved in the biological progresses related with hypoxia adaptation and immune response. In contrast, the genes with favoring expression of cattle alleles have been enriched into different biological progresses, such as secretion of endocrine hormones and lipid metabolism. Our results would support unequal contribution of parental genes to environmental adaptation in the F1 hybrids of cattle and yak.